Determination of some macro and microelements in Thymus moesiacus Velen (Lamiaceae) and its water extracts by atomic absorption spectrometry - Kadifkova-Panovska, Tatjana; Stafilov, Trajče; Bauer, Stevan; Kulevanova, Svetlana; Dorevski, Kiril (Macedonian Journal of Ecology and Environment, 1997)
Content of some macro (Ca, Mg, K, Na, Fe, Zn and Mn) and microelements (Cd, Co, Cr. Cu. Ni and Pb) in Thymus moesiacus Velen. (Lamiaceae) and its water extracts were determined by atomic absorption spectrometry. Distribution of the investigated elements was examined as well as the influence of the duration of extraction of these elements in their water extracts. It was found that the value of extraction for macroelements was under 12 5% while for micrioelements the value was higher, almost 55%.